A influência dos contextos de produção na carga de trabalho de profissionais de segurança privada. - Greghi, Marina Fonseca (2007)
The literature affirms that on the last four decades has been occurring a significant raising on the number of private security companies in all over the world. In Brazil, there are estimations which point that there are 1,148 million people working as agents of private security, and this number can reach the house of 2 million people if considered the informal workers. Besides that, there are not many studies about the worker s activities on private security. This paper analyses the activity of the private security officers. It has been utilized foundation from Work Ergonomic Analysis to understand how the operator manages his workload. This paper provides findings about the perception of the private security officers that the mental workload prevails in the activity and that the main constraints are linked with the work organization, including shift work, control and supervision; and variables of consumer attendance. It is concluded that the Context of Production and Service, based on main aspects of work organization, as: prescriptions, work processes, demands of quality and productivity, has decisive influence upon the behavior of the operator. The Context of Production and Service is important to define the workload. In the activity of the professionals of private security the work is prescribed by the independent contractor and the private security company. This mediation is not a prescription that can be easily followed, but a source of constant conflicts, and then it finishes making source of constant conflicts that hold multiple dimensions and finish producing overload for the vigilant thing.